Roles of Proximate Determinants of Fertility in Recent Fertility Decline in Ethiopia: Application of the Revised Bongaarts Model - Ahmed Shallo S (Dove Medical Press, 2020)
Seifadin Ahmed Shallo Department of Public Health, College of Medicine and Health Sciences, Ambo University, Ambo, EthiopiaCorrespondence: Seifadin Ahmed Shallo Email Seifadinahmed8226@gmail.comIntroduction: In Ethiopia, the fertility rate declined from 5.4 in 2005 to 4.6 by 2016. Many factors have been contributing to this decline. Understanding the factors contributing to the fertility decline and their level of fertility inhibiting effect has a paramount policy implication in any country. This study aimed to assess the contribution of the four proximate determinants of fertility, ie, contraception use, postpartum infecundity, marriage and abortion rate, to fertility decline in Ethiopia since 2005.Methods: This study used publicly available data from the Ethiopia Demographic and Health Surveys (EDHS) of 2005, 2011 and 2016. The EDHS data were the representative data collected from the reproductive-age women through a cross-sectional study. The revised and fine-tuned Bongaarts model of proximate fertility determinants was used for data analysis. The components needed for the analysis were extracted from the full EDHS data using the STAT compiler. Finally, the analysis was done using Microsoft Excel.Results: Of the four proximate determinants of fertility, postpartum insusceptibility contributed the highest fertility inhibiting effect in all three EDHS, and its level was also more prominent among the poorest women. While post partum infecundity, marriage and abortion had a relatively constant effect on fertility over the last 15 years, the fertility inhibiting effect of contraceptive use significantly increased from 15% to 37%.Conclusion: In conclusion, fertility variation in Ethiopia is largely due to the three intermediate determinants of fertility. Over the last one and half decades, contraceptive use was the single most important determinant responsible for fertility decline in Ethiopia. To achieve fertility at replacement level, the country needs a contraceptive prevalence rate of 69%, an increment of nearly 100% from its current contraceptive prevalence rate.Keywords: proximate determinants, Bongaarts revised model, Ethiopia